P–788 Health outcomes at birth, 12 and 24 months of 747 children conceived after Preimplantation Genetic Testing: a single centre experience. (6th August 2021) - Trevisan, L; Forzano, F; Khalaf, Y; Tomlinson, C; Renwick, P; Davies, A; Bint, S; Semple, M; Deshpande, C; Flinter, F; Lashwood, A; Ashraf, T
Abstract: Study question: Does conception by Preimplantation Genetic Testing (PGT-M, PGT-SR) adversely affect health outcomes in children born through this assisted reproductive technique? Summary answer: No significant difference was noted in the rate of congenital malformations in children born after PGT-M and PGT-SR compared with IVF-ICSI children. What is known already: It is already known that the risk of congenital anomalies in IVF-ICSI pregnancies is higher when compared with pregnancies conceived naturally. Study design, size, duration: This is a prospective study on 747 children born between December 1999 and July 2016 after a cycle of PGT-M or PGT-SR (IVF +/- ICSI + embryo biopsy) performed at a single London reproductive centre. PGT-A is not performed in the Centre, so pregnancy outcomes in this group are not relevant. The children were examined at birth, at 12 and 24 months of age and the data collected in three questionnaires. Participants/materials, setting, methods: 747 PGT-M and PGT-SR children were enrolled in the study. 742/747 were examined at birth, 444/747 at 12 months and 168/747 at 24 months. The assessment consisted of three separate questionnaires completed at birth, 12 months and two years of age. The first questionnaire focused on the detection of congenital anomalies in newborn babies. The questionnaire at follow up recorded growth data and examination of the baby's health and development. Main results and the role of chance: We found no evidence that PGT-M and PGT-SR increased the risk of an adverse perinatal outcome when compared with children born after IVF-ICSI. The overall malformation rate in our group of live born after PGT-M and PGT-SR was 3.9% and of major malformations was 2%. These values are comparable with literature data on malformation risk in children born after IVF-ICSI. In terms of misdiagnosis, we had one misdiagnosis of SMA type 1 in 658 pregnancies obtained. This was very early on in the centre's experience of offering PGT-M. Follow-up visits in our cohort allowed us to evaluate their development. Unfortunately, the low participation rate at 24 months (23%) significantly reduced the size of our cohort. We observed a cumulative value of 10% at 24 months of babies with developmental delay which is comparable with the value of 10% given by the WHO, but is twice the incidence Global Research on Developmental Disabilities Collaborators described in the UK in 2016 (4.6%). To our knowledge, no large studies have assessed the risk of developmental delay in children born after PGT. We cannot draw conclusions on this from our small cohort at 24 months and recommend further studies. Limitations, reasons for caution: Although our sample is one of the largest reported, it is too small to generalise results due to the heterogeneity of the conditions for which PGT was being offered and the rarity of these conditions. There were multiple confounding factors including couple's fertility background, varying fertility treatments and embryological techniques. Wider implications of the findings: Our results support published literature highlighting the safety of PGT-M and PGT-SR techniques. We followed up at birth, 12 months and 24 months a large cohort of children, in one of the largest datasets published so far. Trial registration number: Not applicable